2007
DOI: 10.1002/ajmg.a.31847
|View full text |Cite
|
Sign up to set email alerts
|

A girl with duplication 9q34 syndrome

Abstract: We report on a 17-year-old female with numerous developmental abnormalities associated with 46,XX,dup(9)(q33.3q34.1), where the duplication occurred de novo. The patient presented with dysmorphic features and notable psychomotor delays, manifestations similar to those described in other reported cases of duplication of 9q34-qter. Due to late presentation and diagnosis, our patient was not evaluated and characterized until adolescence, when particular attention was paid to the development of secondary sexual ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 12 publications
(11 reference statements)
1
21
0
Order By: Relevance
“…A 9q34 duplication syndrome (9q34 DS) has been reported [10], involving both interstitial [11][12][13][14] and terminal [1,10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] duplications, with different sizes. The associated manifestations include initial poor feeding and thriving, hypotonia, DD, mostly affecting speech and language, ID, craniofacial dysmorphisms and other musculoskeletal anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…A 9q34 duplication syndrome (9q34 DS) has been reported [10], involving both interstitial [11][12][13][14] and terminal [1,10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] duplications, with different sizes. The associated manifestations include initial poor feeding and thriving, hypotonia, DD, mostly affecting speech and language, ID, craniofacial dysmorphisms and other musculoskeletal anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…Reported cases presented with a variety of clinical features depending on the size of the duplication and the presence of other chromosomal abnormalities [Allderdice et al, 1983;Hodou et al, 1987;Spinner et al, 1993;Gawlik-Kuklinska et al, 2007;Youngs et al, 2010]. Our patients had a 9q34.1-qter duplication and partial 13p monosomy due to a translocation between 9q34.1 and 13pter in their healthy mother.…”
Section: Discussionmentioning
confidence: 76%
“…The following (131.7 Mb) in both patients (lower panels of A and B), which indicated that the size of the duplication was approximately 8.5 Mb according to NCBI human genome build 36.3. features were common to both patients in these reports: hypotonia, intellectual disability, developmental delay, characteristic head and facial features associated with dolichocephaly, facial asymmetry, narrow palpebral fissures, deep-set eyes, long nose, prominent chin, microstomia, microretrognathia, and characteristic features of the extremities, including long thin fingers and toes and camptodactyly (Table I). Gawlik-Kuklinska et al [2007] concluded a 7. duplicated region in their patient was critical for the phenotypes they observed (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with distal 9q duplication are described to have facial dysmorphism that included dolichocephaly, facial asymmetry, deep-set eyes, and micrognathia (Gawlik-Kuklinska et al, 2007). Patients with distal 9q duplication are described to have facial dysmorphism that included dolichocephaly, facial asymmetry, deep-set eyes, and micrognathia (Gawlik-Kuklinska et al, 2007).…”
Section: Discussionmentioning
confidence: 99%